PRODUKTIVITAS HASIL TANGKAPAN DAN KOMODITAS UNGGULAN PERIKANAN TANGKAP KABUPATEN ACEH JAYA - Chaliluddin, Makwiyah A.; Amri, Saiful; Aprilla, Ratna Mutia (Journal Galung Tropika, 2019)
Research on superior commodities in Aceh Jaya District, this study examined the productivity of catches and leading capture fisheries commodities in Aceh Jaya District. The next thing to consider to capture fisheries' productivity was the determination of superior commodities in the management of the capture fisheries sector. The research was conducted on February 1, 2018 until March 31, 2018, located in Aceh Jaya District (including; Ujong Muloh fishing port, Patek fishing port, Rigaih fishing port, and Calang fishing port). Data collection methods were observations, interviews, and tracing literature. The productivity of catches was analyzed using Catch Per Unit Effort (CPUE) calculations for the 5 years (2011-2015), while the determination of superior commodities was analyzed by location quotient (LQ) dan comparative performance index (CPI) analysis. The higher CPUE value was found in tuna, the highest number in 2014 amounting to 5193.3 kg/trip. Superior fishery commodities in Aceh Jaya District were Scomberomorus fish with a CPI analysis value was 1,052.92, followed by Euthynnus affinis (515.54), Caranx ignobilis (398.59), Thunnus (309.18), Engraulidae (263.08) and skipjack (234.58).